Objektskoncentration vid slutavverkning - Svensson, Patrik (2011)
The study is made on behalf of SCA Skog Jämtlands förvaltning which is one of five administration units that SCA Skog consists of. The purpose of the study is to investigate which reduced expenses there are according to spatial concentration of cutting areas. By increasing the spatial concentration of cutting areas it will reduce the need of movements by trailer, also reduce the number of roads that you use during the activities. To be able to perform the study, access to a annual cuttings in nine years have been made available. From this volume new annual cuttings has been created but more concentrated. The two different results have been compared and the results show that concentration of cutting areas generates reduced need for trailer transports and less km road that has to be maintained. But then, if it´s practical viable can be discussed. With an industry that fast rearrange it´s need for raw material and a weather that quickly can change. This involves changes that rapidly can ruin the best of plans. Keywords: Spatial concentration of cutting areas, Singel cutting areas, Costing of forest road, Costing of moves with trailer